Preparation method of sulfur-containing full-formula wet-process mixed rubber composite material

By covering silicon dioxide on the surface of sulfur and hybrid hybrid agent and glue, the problem of relying on dry method in the existing technology to rely on dry method, improve the stability of wet method and comprehensive rubber synthesis Performance has achieved efficient and environmentally friendly production process.

CN119371725AActive Publication Date: 2025-01-28HENAN UNIVERSITY +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411633701.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-28
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing full-formula wet kneading technology still relies on dry kneading during the addition of vulcanizing agents and accelerators, resulting in long drying time, low production efficiency, and failure to fully realize high-temperature drying.

Method used

By covering the silicon on the surface of the sulfur, and the various additives and fillers are mixed with the glue lactation pre -mixed with the glue emulsion, the diversification of the filler and the assistant is improved, and the mixed loss is reduced.

Benefits of technology

It improves the stability of the full -formula moisture mixed glue with a sulfur -containing formula in high temperature drying, avoid pre -sulfide, enhance the comprehensive rubber performance, simplify the processing process, and reduce production energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a preparation method of a sulfur-containing full-formula wet-process mixed rubber composite material. The preparation method comprises the following steps: firstly, preparing silicon dioxide coated sulfur (SiO2 coated S) by adopting a liquid-phase synthesis method, and carrying out spray drying to obtain powder of the silicon dioxide coated sulfur; and preparing the SiO2 (at) S, other reinforcing fillers and various rubber additives into dispersion liquid by adopting a wet mixing process, mixing the dispersion liquid with latex, flocculating, and drying to obtain the SiO2 (at) S full-formula wet mixing rubber composite material. Nano silicon dioxide is coated on the surface of sulfur through liquid phase in-situ growth, and then spray drying is carried out, so that the particle size of powder is effectively controlled, and agglomeration is reduced. The coating of the silicon dioxide is beneficial to improving the stability of the sulfur-containing full-formula wet-process rubber compound in the subsequent high-temperature drying process, and the prevulcanization phenomenon of the sulfur-containing full-formula wet-process rubber compound is avoided; various assistants and fillers are subjected to liquid-phase mixing in advance and then are mixed with rubber latex for flocculent precipitation or are mixed with a rubber solution for solvent evaporation, so that the dispersity of the fillers and the assistants is improved, the mixing loss is reduced, the loss in the addition process of the rubber assistants is reduced, and the comprehensive performance of rubber is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wet-mixed rubber composite materials, and specifically relates to a method for preparing a sulfur-containing full-formula wet-mixed rubber composite material. The prepared wet-mixed rubber can be used in rubber fields such as tires, shoe materials, and tracks. Background Art

[0002] The traditional production and processing of rubber products is mainly based on dry mixing, but its mixing energy consumption is high, the amount of filler added is limited, the dispersion of fillers and additives is poor, and it is harmful to the environment and workers, so it is gradually replaced by wet mixing. At present, wet mixing technology can effectively improve the dispersion of fillers, effectively reduce production energy consumption, and increase the amount of fillers added to the rubber matrix, but most production methods today still add rubber additives to rubber through dry mixing.

[0003] By pre-dispersing the filler and all rubber additives in a suitable solvent through wet mixing, the full-formula wet mixing can be achieved, which can improve the dispersibility of the filler and rubber additives in the rubber matrix and greatly reduce the energy consumption of subsequent rubber processing and mixing. At the same time, the full-formula wet mixing technology can improve the comprehensive performance of rubber and achieve environmental protection, energy saving and efficient production. At present, there are related technical patents, for example: a method for preparing a white carbon black / natural rubber composite material disclosed in Chinese patent CN 111171390 B, which uses a wet mixing process to prepare white carbon black into a uniform dispersed solution through mechanical grinding, and after mixing with natural latex, slowly stir to make the natural latex and white carbon black fully contact, and use the positive charge generated by high-temperature atomization to flocculate the negatively charged natural latex and wrap the white carbon black therein, and then dehydrate and dry to obtain a white carbon black / natural rubber composite material. Chinese patent CN 114316388 A discloses a low-energy wet mixing rubber and its preparation method, step 1: weigh each raw material component according to the weight; step 2: after mixing the protective agent with the rubber latex, add the activator, accelerator, sulfur, antioxidant and other dispersed and mixed, add the active reinforcing agent, disperse and stir until it is viscous and condensed; step 3: the condensed emulsion is subjected to double-roll extrusion and naturally air-dried to obtain the wet mixing raw rubber. Chinese patent CN 105690587 B discloses a rubber wet mixing method of first atomizing and then mixing, the materials are prepared into various solutions respectively, and after atomization, they enter the mixing chamber to complete diffusion, contact, mixing and complete wet mixing, thereby achieving the mixing effect, and the atomized solution is condensed and collected and then stirred to obtain a rubber compound.

[0004] However, the existing full-formula wet mixing technology only realizes the wet mixing of fillers and some additives, and the vulcanizer and accelerator are still added by dry mixing in an open mill or internal mixer; or the full-formula wet mixing technology does not fully realize high-temperature drying, which will lead to long drying time and low production efficiency in actual production. Therefore, in order to further optimize the process and expand the scope of application of full-formula wet mixing, this application is developed. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a fully formulated wet mixed rubber composite material containing sulfur. The method helps to improve the stability of the fully formulated wet mixed rubber containing sulfur in a subsequent high-temperature drying process by coating silicon dioxide on the surface of sulfur, thereby avoiding pre-vulcanization thereof; various additives and fillers are pre-mixed in liquid phase and then mixed with latex for flocculation and precipitation, which is beneficial to improving the dispersibility of fillers and additives, reducing mixing losses, reducing losses in the process of adding rubber additives, and enhancing the comprehensive performance of rubber.

[0006] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a sulfur-containing full-formula wet-mixed rubber composite material comprises the following steps: 1) Liquid phase synthesis to prepare SiO2@S dispersion: Sulfur is dispersed in a reaction medium using a surfactant, polymer or nanopowder, and sodium silicate or silicate is hydrolyzed in the reaction medium and adsorbed on the surface of sulfur, followed by aging, and further hydrolysis on the sulfur surface to form a dense silica shell to obtain SiO2@S dispersion; 2) Spray drying: The SiO2@S dispersion is mixed with a binder and spray dried to granulate to obtain SiO2@S powder; 3) Preparation of a sulfur-containing water-based fully formulated wet-mixed rubber composite material: disperse the reinforcing filler in a certain amount of pure water, add a vulcanizing agent, a silane coupling agent, an antioxidant, a protective wax, an activator, and an accelerator in sequence, and obtain a water dispersion of the filler and the fully formulated additives by heating and stirring; separately prepare a dispersion of a certain concentration of a flocculant into a dispersion of a second; mix the rubber latex with the water dispersion of the first and the dispersion of the second, stir and flocculate, filter, and dry to obtain a sulfur-containing fully formulated wet-mixed rubber composite material; Alternatively, a sulfur-containing oil-based fully formulated wet-mixed rubber composite material is prepared by dispersing a reinforcing filler in a certain amount of an organic solvent or pure water, adding a vulcanizing agent, a silane coupling agent, an antioxidant, a protective wax, an activator, and an accelerator, and obtaining an emulsified dispersion of the filler and the fully formulated additives by heating and stirring, mixing the oil-based rubber solution with the emulsified dispersion, distilling under reduced pressure, and drying to obtain the composite material.

[0007] Specifically, the sulfur includes but is not limited to one or two of sublimated sulfur, oil-extended sulfur, etc.; the reaction medium can be one or more combinations of water, C2-C12 alcohols, acetone, etc.

[0008] Specifically, the surfactant can be one or more of anionic surfactants such as sulfonates, carboxylates, sulfates and phosphates, cationic surfactants such as quaternary ammonium salts, amine salts, and heterocyclic types, nonionic surfactants such as polyoxyethylene type, polyol type, polyether type, alkanolamide type, and zwitterionic surfactants such as amino acid type, betaine type, etc.; the polymer is one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, etc.; the nano powder is one or more of silicon dioxide, titanium dioxide, calcium carbonate, zinc oxide, kaolin, magnesium oxide, etc.; the amount of the surfactant or polymer or nano powder is 1%-10% of the mass of sulfur, the dispersion time is 1-3h, and the dispersion temperature is 20°C-80°C.

[0009] Specifically, the silicate is a C1-C6 orthosilicate, and the concentration in the reaction medium is 0.1-5 mol / L; the concentration of sodium silicate in the reaction medium is 0.1 mol / L-5 mol / L; the amount of sodium silicate or silicate modified with sulfur is 3%-10%, the hydrolysis reaction temperature is 40°C-80°C, the hydrolysis reaction time is 1-3h, the stirring aging time is 1-3h, and the aging temperature is 20°C-80°C.

[0010] Furthermore, the hydrolysis reaction occurs between pH 3 and 11, and the pH can be adjusted by acid, ammonia water or ammonium salt solution. The usable acid is inorganic acid and organic acid, including but not limited to inorganic acids such as hydrochloric acid and sulfuric acid, and water-soluble organic acids with carboxyl groups, sulfonic acid groups, sulfinic acid groups, and thiocarboxylic acid groups, such as citric acid, formic acid, acetic acid, etc.

[0011] Further, the binder is one or more of saturated or unsaturated polymers such as natural rubber latex, styrene-butadiene rubber emulsion, itaconate rubber emulsion, chloroprene rubber emulsion, polyurethane rubber emulsion, nitrile rubber emulsion, polyvinyl acetate emulsion, gum arabic, gelatin, dextrin, cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, etc., and the amount used is 1%-42% of the mass of sulfur. When the binder is natural rubber latex, styrene-butadiene rubber emulsion, itaconate rubber emulsion, chloroprene rubber emulsion, polyurethane rubber emulsion, nitrile rubber emulsion, polyvinyl acetate emulsion, it is further preferred that the amount of the binder is 1%-30% of the mass of sulfur in terms of solid content. The inlet temperature of the spray drying is 150°C-300°C, the outlet temperature is 100°C-150°C, the solid content of the SiO2@S dispersion is 5%-30%, and the feed speed is 5-100rpm.

[0012] Specifically, the vulcanizing agent can be one or more of sublimated sulfur, oil-extended sulfur, SiO2@S powder, etc.; the reinforcing filler can be one or more of silica, calcium carbonate, carbon black, duplex carbon black, pyrolysis carbon black, titanium dioxide, reactive silica, waste rubber powder, modified waste rubber powder, etc.; among which the reactive silica is purchased from Henan Heda Nanomaterials Engineering Research Center Co., Ltd., and its surface has one or more functional groups of thiol, polysulfide, epoxy, amino, and double bond. The silane coupling agent can be an organic chain segment and functional group containing 1-3 silicon-carbon bonds, the organic chain contains 1-12 carbon atoms, and the functional group includes one or more of thiol, polysulfide, epoxy, amino, double bond, etc.; the antioxidant includes one or more of ketoamines, aldehyde amines, diaryl secondary amines, diphenylamines, p-phenylenediamines and alkyl aromatic secondary amines; the protective wax includes one or more mixtures of paraffin wax, microcrystalline wax, polyethylene wax, etc.; the activator is one or more of zinc oxide, magnesium oxide, lead oxide, stearic acid, amine, etc.; the promoter includes one or more of thioureas, aldehyde amines, guanidines, thiazoles, sulfonamides, thiurams, dithiocarbamates, xanthates, etc.

[0013] Specifically, the rubber includes water-based rubber latex and oil-based rubber solution (oil-based rubber is dissolved in an organic solvent to obtain a solution). The water-based rubber latex includes natural rubber latex and synthetic rubber emulsion, including but not limited to one or more mixtures of natural rubber latex, styrene-butadiene rubber emulsion, itaconate rubber emulsion, chloroprene rubber emulsion, polyurethane rubber emulsion, nitrile rubber emulsion, etc. The oil-based rubber solution (oil-based rubber is dissolved in an organic solvent to obtain a solution, which is distinguished from synthetic rubber emulsion) includes but not limited to one or more mixtures of oil-based rubbers such as soluble styrene-butadiene rubber, EPDM rubber, butadiene rubber, styrene-propylene rubber, etc. The total solid content of the rubber component in the water dispersion or emulsified dispersion is 1%-60%. The flocculant includes but is not limited to one or more of formic acid, acetic acid, sodium chloride, calcium chloride, magnesium chloride, zinc sulfate, aluminum sulfate, etc. The oil-based rubber solution does not need to add a flocculant. The organic solvent includes but is not limited to one or more of benzene, toluene, n-hexane, cyclohexane, etc.

[0014] Further, in step 3), the amount of each raw material is as follows: 60-140 parts of rubber dry glue, 30-70 parts of reinforcing filler, 0.1-5 parts of vulcanizing agent, 3-7 parts of silane coupling agent, 0.1-5 parts of antioxidant, 0.1-5 parts of protective wax, 0.1-10 parts of activator, 0.1-5 parts of accelerator, 6-14 parts of flocculant, wherein the water-based rubber latex or oil-based rubber solution is measured based on the rubber dry glue. Further preferably, based on 100 parts of rubber dry glue, the amount of flocculant is 6-14 parts.

[0015] Preferably, the method for preparing the sulfur-containing full-formula wet-mixed rubber composite material comprises the following specific steps: 1) Preparation of sulfur-containing water-based full-formulation wet mixing rubber composite materials: Step 1: Disperse the reinforcing filler in a certain amount of pure water to prepare a dispersion with a solid content of 5%-20%, and stir and disperse it with a sand mill at a speed of 1200-1800rpm for 20-60min; Step 2: Add vulcanizing agent, stir and disperse with sand mill, speed 1200-1800rpm, time 20-60min; Step 3: Add silane coupling agent, stir and disperse with sand mill, speed 1200-1800rpm, time 20-60min; Step 4: Add antioxidant, protective wax, some activators and other oily additives, heat and stir in a sand mill to disperse, and emulsify and disperse the polymer or special functional group grafted on the surface of reactive silica in the water dispersion, heat the reaction temperature to 60-90°C, rotate at 1200-1800rpm, and last for 20-60min; Step 5: Add the remaining activator and promoter, stir and disperse with a sand mill at a speed of 1200-1800 rpm for 20-60 min to obtain an aqueous dispersion of filler and full formula additives; Step 6: prepare the flocculant into a dispersion liquid 2 of a certain concentration, wherein the solid content of the dispersion liquid 2 is 1%-15%; Step 7: dilute the rubber latex to a solid content of 5%-40%, mix it with the above-mentioned aqueous dispersion 1 and dispersion 2, stir and flocculate, filter, and dry to obtain a water-based full-formula wet-mixed rubber composite material containing sulfur.

[0016] 2) Preparation of sulfur-containing oil-based full-formulation wet mixing rubber composite materials: Step 1: Disperse the reinforcing filler in a certain amount of organic solvent to prepare a dispersion with a solid content of 5%-20%, and disperse by mechanical stirring at a speed of 200-1000rpm for 20-60min; Step 2: Add vulcanizing agent, silane coupling agent, antioxidant, protective wax, activator, and accelerator, disperse by mechanical stirring, and heat at a speed of 200-1000 rpm for 20-60 min; Step 3: recover the organic solvent by vacuum distillation and dry it to obtain an oil-based full-formula wet-mixed rubber composite material containing sulfur.

[0017] The innovation of the present invention is as follows: first, nano-silicon dioxide is coated on the surface of sulfur through in-situ growth in liquid phase, and then spray-dried to effectively control the particle size of the powder and reduce agglomeration. Second, the coating of silicon dioxide helps to improve the stability of the fully formulated wet mixed rubber containing sulfur in the subsequent high-temperature drying process, and avoids the pre-vulcanization phenomenon; third, various additives and fillers are pre-mixed in liquid phase, and then mixed with latex for flocculation and precipitation, which is beneficial to improve the dispersibility of fillers and additives, reduce mixing losses, and reduce the loss of rubber additives in the process of adding rubber additives, and enhance the comprehensive performance of rubber; fourth, the fully formulated wet mixed rubber containing sulfur can be directly vulcanized and processed into products by downstream users, reducing mixing steps, reducing production energy consumption, and saving production costs.

[0018] Compared with the prior art, the present invention has the following beneficial effects: The present invention first introduces a vulcanizing agent into a fully formulated wet mixed rubber, further simplifies the processing technology of rubber, reduces processing energy consumption, and facilitates processing and molding by downstream manufacturers. And by coating sulfur with silicon dioxide, the performance of the fully formulated wet mixed rubber is improved. Specifically, it has the following advantages: ① The coating of silicon dioxide helps to improve the stability of the fully formulated wet mixed rubber containing sulfur in the subsequent high-temperature drying process, and avoids the occurrence of pre-vulcanization; ② Various additives and fillers are pre-mixed in liquid phase, and then mixed with latex for flocculation and precipitation, which is beneficial to improve the dispersibility of fillers and additives, reduce mixing losses, and reduce losses in the process of adding rubber additives, thereby enhancing the comprehensive performance of rubber; ③ The fully formulated wet mixed rubber containing sulfur can be directly vulcanized into products by downstream users, reducing mixing steps, reducing production energy consumption, and saving production costs. DETAILED DESCRIPTION

[0019] The following is a complete and clear description of the technical solutions in the embodiments of the present invention. The described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following is only a better embodiment of the present invention, which is only used to explain the present invention and cannot be understood as limiting the scope of the patent of the present invention. That is, the protection scope of the present invention is not limited to this.

[0020] Unless otherwise specified, all raw materials used are common commercial products that can be purchased directly, or can be prepared by conventional methods in the art. For example, reactive white carbon black was purchased from Henan Heda Nanomaterial Engineering Research Center Co., Ltd., such as model 251, 308, 315, etc., and model 251 reactive white carbon black was used in the following examples and comparative examples; antioxidant was purchased from Shengao Chemical Technology Co., Ltd., model 4020. Among them, phr refers to mass fraction.

[0021] The present invention is further described below by way of examples.

[0022] Example 1 Weigh 20 g of sublimed sulfur, 1.00 g of PEG-4000 polyethylene glycol-4000, and 1.00 g of CTAB hexadecyltrimethylammonium bromide, add 178.00 g of pure water, and prepare a dispersion with a solid content of 10%. Stir at a speed of 300-500 rpm and ultrasonically stir at room temperature for 1 hour to obtain a sulfur dispersion.

[0023] Based on a silica modification amount of 6%, weigh 5.00 g of sodium silicate and 3.00 g of sulfuric acid (pre-prepared to a concentration of 20%), and add 19.41 g and 23.89 g of pure water respectively to prepare the concentrations to 1.00 mol / L and 0.25 mol / L.

[0024] The prepared sodium silicate solution and sulfuric acid solution are flowed into the sulfur dispersion in parallel for 2 hours, the reaction temperature is 40°C, the pH value is 9, and the stirring speed is controlled at 300-500rpm. After the parallel flow reaction is completed, it is aged at a constant temperature for 2 hours to form a silica shell on the sulfur surface.

[0025] The sulfur dispersion after the reaction was mixed with 8.33 g of styrene-butadiene rubber latex (solid content 60%), with a stirring speed of 800 rpm for 30 min, and SiO2@S powder was obtained by spray drying, with an inlet air temperature of 180-220°C, an outlet air temperature of 100-120°C, and a feed rate of 25 rpm.

[0026] 50 phr of reactive silica was dispersed in 450 phr of pure water to prepare a water dispersion with a solid content of 10%. The dispersion was stirred and dispersed by a sand mill at a speed of 1500 rpm for 30 minutes.

[0027] Add 1.5phr of vulcanizing agent SiO2@S powder and stir and disperse it with a sand mill at a speed of 1500rpm for 30min.

[0028] Add 5phr of silane coupling agent Si-69, stir and disperse with a sand mill at a speed of 1500rpm for 30min.

[0029] Add 1.5phr antioxidant 4020, 1.5phr microcrystalline wax, and 1.5phr stearic acid, heat and stir to disperse in a sand mill, the reaction temperature is 90°C, the speed is 1500rpm, and the time is 30min.

[0030] Add 1.5phr zinc oxide, 2phr accelerator CZ, 1phr accelerator D, stir and disperse with a sand mill at a speed of 1500rpm for 30min to obtain an aqueous dispersion of filler and full formula additives.

[0031] 10 phr of flocculant calcium chloride was prepared into dispersion 2 with a solid content of 10%.

[0032] Taking the dry natural rubber mass as 100phr, 166.7phr of concentrated natural latex with a solid content of 60% (preservative ammonia content: 0.6%, Hainan Natural Rubber Industry Group Co., Ltd., the same below) was diluted to 30%, mixed with the above two aqueous dispersions 1 and 2, stirred for flocculation, filtered, and dried to obtain a sulfur-containing full-formula wet-mixed rubber composite material.

[0033] The sulfur-containing full-formula wet-mixed rubber composite material prepared as described above was plasticized and formed on an open mill to obtain a full-formula rubber composite material mix, which was then vulcanized (vulcanization temperature: 150°C, vulcanization time: T90+5min, vulcanization pressure 20MPa) to prepare a vulcanized test piece, and relevant performance tests were performed. The results are shown in Table 1.

[0034] Example 2 Weigh 20.00 g of sublimed sulfur, 1.00 g of CTAB, and 1.00 g of OP-10 dodecylphenol polyoxyethylene ether, add 178.00 g of pure water, and prepare a dispersion with a solid content of 10%. Stir at a speed of 300-500 rpm and ultrasonically stir at room temperature for 1 hour to obtain a sulfur dispersion.

[0035] Based on a silica modification amount of 5%, weigh 4.12 g of sodium silicate and 2.50 g of sulfuric acid (pre-prepared to a concentration of 20%), and add 16.16 g and 19.91 g of pure water respectively to prepare the concentrations to 1.00 mol / L and 0.25 mol / L.

[0036] The prepared sodium silicate solution and sulfuric acid solution are flowed into the sulfur dispersion in parallel for 1.5 hours, the reaction temperature is 40°C, the pH value is 9, and the stirring speed is controlled at 300-500rpm. After the parallel flow reaction is completed, it is aged at a constant temperature for 2 hours to form a silica shell on the sulfur surface.

[0037] The reacted sulfur dispersion was mixed with 7.27 g natural rubber latex (solid content 55%), stirred at 800 rpm for 30 min, and SiO2@S powder was obtained by spray drying, with an inlet air temperature of 180-220°C, an outlet air temperature of 100-120°C, and a feed rate of 25 rpm.

[0038] 50 phr of reactive silica was dispersed in 450 phr of pure water to prepare a water dispersion with a solid content of 10%, and the dispersion was stirred and dispersed by a sand mill at a speed of 1700 rpm for 30 minutes.

[0039] Add 1.5phr of vulcanizing agent SiO2@S powder and stir and disperse it with a sand mill at a speed of 1700rpm for 30min.

[0040] 5 phr of silane coupling agent Si-69 was added, and the mixture was dispersed by stirring on a sand mill at a speed of 1700 rpm for 30 min.

[0041] Add 1.5phr antioxidant 4020, 1.5phr microcrystalline wax, and 1.5phr stearic acid, heat and stir to disperse in a sand mill, the reaction temperature is 90°C, the rotation speed is 1700rpm, and the time is 30min.

[0042] Add 1.5phr zinc oxide, 2phr accelerator CZ, 1phr accelerator D, stir and disperse with a sand mill at a speed of 1700rpm for 30min to obtain an aqueous dispersion of filler and full formula additives.

[0043] 10 phr of flocculant calcium chloride was prepared into dispersion 2 with a solid content of 10%.

[0044] With the dry mass of styrene butadiene rubber being 100phr, 500phr of styrene butadiene rubber latex with a solid content of 20% is mixed with the two aqueous dispersions 1 and 2, stirred for flocculation, filtered, and dried to obtain a S@SiO2 full-formula wet-mixed rubber composite material.

[0045] The fully formulated wet-mixed rubber composite material prepared as described above was plasticized and formed on an open mill to obtain a fully formulated rubber composite material mix, which was then vulcanized (vulcanization temperature: 150°C, vulcanization time: T90+5min, vulcanization pressure 20MPa) to prepare a vulcanized test piece, and relevant performance tests were performed. The results are shown in Table 1.

[0046] Comparative Example 1 Based on the mass of natural rubber dry rubber as 100 parts, 100 parts of natural rubber dry rubber were weighed, and 50 parts of reactive white carbon black, 5 parts of silane coupling agent Si-69, 1.5 parts of antioxidant 4020, 1.5 parts of microcrystalline wax, 1.5 parts of stearic acid, 5 parts of activator zinc oxide, 2 parts of accelerator CZ, 1 part of accelerator D, and 1.5 parts of S were added by dry mixing to obtain dry mixed rubber. Then vulcanization (vulcanization temperature: 150℃, vulcanization time: T90+3min, vulcanization pressure 20MPa) was performed to prepare vulcanized test pieces, and relevant performance tests were carried out. The results are shown in Table 1.

[0047] Comparative Example 2 50phr of reactive white carbon black was dispersed in 450phr of pure water to prepare a water dispersion with a solid content of 10%, and the dispersion was stirred and dispersed by a sand mill at a speed of 1700rpm for 30min to obtain a filler water dispersion 1. 10phr of flocculant calcium chloride was prepared into a dispersion 2 with a solid content of 10%, based on the mass of natural rubber dry rubber being 100phr. 166.7phr concentrated natural latex with a solid content of 60% (preservative ammonia content: 0.6%, Hainan Natural Rubber Industry Group Co., Ltd., the same below) was diluted to 30%, mixed with the above two aqueous dispersions 1 and 2, stirred for flocculation, filtered, and dried to obtain a wet masterbatch, and 5 parts of silane coupling agent Si-69, 1.5 parts of antioxidant 4020, 1.5 parts of microcrystalline wax, 1.5 parts of stearic acid, 5 parts of activator zinc oxide, 2 parts of accelerator CZ, 1 part of accelerator D, and 1.5 parts of S were added to the open mill to obtain a wet mixed rubber. Then vulcanization (vulcanization temperature: 150℃, vulcanization time: T90+3min, vulcanization pressure 20MPa) was performed to prepare a vulcanized test piece, and relevant performance tests were carried out. The results are shown in Table 1.

[0048] Comparative Example 3 Based on the mass of styrene-butadiene rubber dry rubber as 100 parts, 100 parts of styrene-butadiene rubber dry rubber were weighed, and 50 parts of reactive white carbon black, 5 parts of silane coupling agent Si-69, 1.5 parts of antioxidant 4020, 1.5 parts of microcrystalline wax, 1.5 parts of stearic acid, 5 parts of activator zinc oxide, 2 parts of accelerator CZ, 1 part of accelerator D, and 1.5 parts of S were added by dry mixing to obtain dry mixed rubber, which was then vulcanized (vulcanization temperature: 150°C, vulcanization time: T90+3min, vulcanization pressure 20MPa) to prepare vulcanized test pieces, and relevant performance tests were carried out. The results are shown in Table 1.

[0049] Comparative Example 4 50phr of reactive white carbon black was dispersed in 450phr of pure water to prepare a water dispersion with a solid content of 10%, and the mixture was dispersed by stirring in a sand mill at a speed of 1700rpm for 30min. A filler water dispersion was obtained. 10phr of flocculant calcium chloride was prepared into a dispersion with a solid content of 10%. The dry rubber mass of styrene-butadiene rubber was 100phr. 500phr of styrene-butadiene rubber latex with a solid content of 20% was mixed with the above two water dispersions 1 and 2, stirred for flocculation, filtered, and dried to obtain a wet masterbatch. 5 parts of silane coupling agent Si-69, 1.5 parts of antioxidant 4020, 1.5 parts of microcrystalline wax, 1.5 parts of stearic acid, 5 parts of activator zinc oxide, 2 parts of accelerator CZ, 1 part of accelerator D, and 1.5 parts of S were added to an open mill to obtain a wet mixed rubber. Then, the vulcanization was carried out (vulcanization temperature: 150°C, vulcanization time: T90+3min, vulcanization pressure 20MPa) to make vulcanization test pieces, and relevant performance tests were carried out. The results are shown in Table 1.

[0050] Table 1 Performance test As shown in Table 1, under fixed formula conditions, the vulcanized rubber properties of the mixed rubbers prepared by different mixing methods are significantly different. In the preparation process of the full-formula wet-mixed rubber, various rubber additives and fillers are pre-dispersed to avoid the problem of uneven mixing of rubber additives in the subsequent processing. At the same time, it also reduces the shearing of rubber molecular chains during the plasticizing process, retains more rubber macromolecular chains, and can form more three-dimensional network structures during the vulcanization process. The mechanical properties of the vulcanized rubber of the full-formula wet-mixed rubber are significantly better than those of the dry-mixed rubber and the wet-mixed rubber.

Claims

1. A method for preparing a sulfur-containing full-formula wet-mixed rubber composite material, characterized in that: The steps include: 1) Preparation of SiO2@S dispersion by liquid phase synthesis: Sulfur is dispersed in a reaction medium using a surfactant, polymer or nanopowder, and hydrolyzed in the reaction medium using sodium silicate or silicate, followed by aging to obtain a SiO2@S dispersion; 2) Spray drying: The SiO2@S dispersion is mixed with a binder and spray dried to granulate to obtain SiO2@S powder; 3) Preparation of sulfur-containing water-based full-formula wet-mixed rubber composite materials: disperse reinforcing fillers in a certain amount of pure water, add vulcanizing agent, silane coupling agent, antioxidant, protective wax, activator, and accelerator, and obtain a water dispersion of fillers and full-formula additives by heating and stirring; separately prepare a dispersion of a certain concentration of flocculant into a dispersion of a second; mix water-based rubber latex with the water dispersion of the first and the dispersion of the second, stir and flocculate, filter, and dry to obtain; Alternatively, a sulfur-containing oil-based fully formulated wet-mixed rubber composite material is prepared by dispersing a reinforcing filler in a certain amount of an organic solvent or pure water, adding a vulcanizing agent, a silane coupling agent, an antioxidant, a protective wax, an activator, and an accelerator, and obtaining an emulsified dispersion of the filler and the fully formulated additives by heating and stirring, mixing the oil-based rubber solution with the emulsified dispersion, distilling under reduced pressure, and drying to obtain the composite material.

2. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The sulfur includes but is not limited to one or both of sublimated sulfur and oil-extended sulfur; the reaction medium is one or more combinations of water, C2-C12 alcohol, and acetone.

3. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The surfactant is one or more of anionic surfactants such as sulfonates, carboxylates, sulfates and phosphates, cationic surfactants such as quaternary ammonium salts, amine salts and heterocyclics, nonionic surfactants such as polyoxyethylene, polyol, polyether and alkanolamide, and zwitterionic surfactants such as amino acids and betaine; the polymer is one or more of polyvinyl alcohol, polyethylene glycol and polyvinyl pyrrolidone; the nano powder is one or more of silicon dioxide, titanium dioxide, calcium carbonate, zinc oxide, kaolin and magnesium oxide; the dosage of the surfactant or polymer or nano powder is 1%-10% of the mass of sulfur, the dispersion time is 1-3h and the dispersion temperature is 20°C-80°C.

4. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The silicate is a C1-C6 orthosilicate, and its concentration in the reaction medium is 0.1-5 mol / L; the concentration of sodium silicate in the reaction medium is 0.1 mol / L-5 mol / L; the amount of sodium silicate or silicate modified with sulfur is 3%-10%, the hydrolysis reaction temperature is 40°C-80°C, the aging time is 1-3h, and the aging temperature is 20°C-80°C.

5. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The hydrolysis reaction occurs between pH 3 and 11, and the pH is adjusted with acid, ammonia water or ammonium salt solution. The acids that can be used are inorganic acids and organic acids, including but not limited to inorganic acids such as hydrochloric acid and sulfuric acid, and water-soluble organic acids with carboxyl groups, sulfonic acid groups, sulfinic acid groups, and thiocarboxylic acid groups, such as citric acid, formic acid, acetic acid, etc.

6. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The binder is one or more of saturated or unsaturated polymers such as natural rubber latex, styrene-butadiene rubber emulsion, itaconate rubber emulsion, chloroprene rubber emulsion, polyurethane rubber emulsion, nitrile rubber emulsion, polyvinyl acetate emulsion, gum arabic, gelatin, dextrin, cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, etc., and the amount used is 1%-42% of the mass of sulfur; the inlet temperature of the spray drying is 150℃-300℃, the outlet temperature is 100℃-150℃, the solid content of the SiO2@S dispersion is 5%-30%, and the feed speed is 5-100rpm.

7. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The vulcanizing agent is one or more of sublimated sulfur, oil-extended sulfur, and SiO2@S powder; the reinforcing filler is one or more of calcium carbonate, white carbon black, carbon black, dual-phase carbon black, pyrolysis carbon black, titanium dioxide, reactive white carbon black, waste rubber powder, and modified waste rubber powder; the silane coupling agent is an organic chain segment and functional group containing 1-3 silicon-carbon bonds, the organic chain contains 1-12 carbon atoms, and the functional group includes one or more of mercapto, polysulfide, epoxy, amino, and double bond; the anti- The aging agent includes one or more of ketoamines, aldehyde amines, diaromatic secondary amines, diphenylamines, p-phenylenediamines and alkyl aromatic secondary amines; the protective wax includes one or more mixtures of paraffin wax, microcrystalline wax and polyethylene wax; the activator is one or more of zinc oxide, magnesium oxide, lead oxide, stearic acid and amines; the accelerator includes one or more of thioureas, aldehyde amines, guanidines, thiazoles, sulfonamides, thiurams, dithiocarbamates and xanthates.

8. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The rubber includes water-based rubber latex and oil-based rubber solution (oil-based rubber is dissolved in an organic solvent to obtain a solution), and the total solid content of the rubber component in the water dispersion or the emulsified dispersion is 1%-60%; the flocculant includes but is not limited to one or more of formic acid, acetic acid, sodium chloride, calcium chloride, magnesium chloride, zinc sulfate, and aluminum sulfate, wherein the oil-based rubber solution does not need to add a flocculant; the organic solvent includes but is not limited to one or more of benzene, toluene, n-hexane, cyclohexane, etc.

9. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: In step 3), the amount of each raw material is, by weight, 60-140 parts of rubber dry glue, 30-70 parts of reinforcing filler, 0.1-5 parts of vulcanizing agent, 3-7 parts of silane coupling agent, 0.1-5 parts of antioxidant, 0.1-5 parts of protective wax, 0.1-10 parts of activator, 0.1-5 parts of promoter, and 6-14 parts of flocculant, wherein the water-based rubber latex and the oil-based rubber solution are measured based on the rubber dry glue.

10. The method for preparing the sulfur-containing full-formula wet-mixed rubber composite material according to claim 1, characterized in that: The specific steps are as follows: 1) Preparation of sulfur-containing water-based full-formulation wet mixing rubber composite materials: Step 1: Disperse the reinforcing filler in a certain amount of pure water to prepare a dispersion with a solid content of 5%-20%, and stir and disperse it with a sand mill at a speed of 1200-1800rpm for 20-60min; Step 2: Add vulcanizing agent, stir and disperse with sand mill, speed 1200-1800rpm, time 20-60min; Step 3: Add silane coupling agent, stir and disperse with sand mill, speed 1200-1800rpm, time 20-60min; Step 4: Add antioxidant, protective wax, and part of activator, heat and stir in a sand mill to disperse, temperature 60-90°C, speed 1200-1800rpm, time 20-60min; Step 5: Add the remaining activator and promoter, stir and disperse with a sand mill at a speed of 1200-1800 rpm for 20-60 min to obtain an aqueous dispersion of filler and full formula additives; Step 6: prepare the flocculant into a dispersion liquid 2 of a certain concentration, wherein the solid content of the dispersion liquid 2 is 1%-15%; Step 7: dilute the rubber latex to a solid content of 5%-40%, mix it with the water dispersion 1 and the dispersion 2, stir and flocculate, filter, and dry to obtain; 2) Preparation of sulfur-containing oil-based full-formulation wet mixing rubber composite materials: Step 1: Disperse the reinforcing filler in a certain amount of organic solvent to prepare a dispersion with a solid content of 5%-20%, and disperse by mechanical stirring at a speed of 200-1000rpm for 20-60min; Step 2: Add vulcanizing agent, silane coupling agent, antioxidant, protective wax, activator, and accelerator, disperse by mechanical stirring, and heat at a speed of 200-1000 rpm for 20-60 min; Step 3: recover the organic solvent by distillation under reduced pressure and dry to obtain the product.

Citation Information

Patent Citations

  • A wet rubber mixing method of first atomizing and then mixing

    CN105690587B

  • A method for preparing silica / natural rubber composite material

    CN111171390B

  • Low-energy-consumption wet-process mixed rubber and preparation method thereof

    CN114316388A

  • Preparation method of silicon-dioxide-coated sulfur microcapsules

    CN105037802A

  • Method for coating and modifying sulfur

    CN106084292A